The Illusion of Open Access in Shadow Library Practices and Digital Copyright Infringement - Khaulani, Namira; Siti Royani, Nabila; Oktaviani Rahma, Nadya; Shifa Nurmaya, Nazwa; Hazima Nugraha, Nabila (VARIA HUKUM, 2025)
Abstract: The transformation of physical books into digital formats has increased information accessibility but also created new challenges, one of which is illegal distribution through shadow libraries such as LibGen, Z-Library, and Sci-Hub. These platforms provide free access to e-books and academic works without the permission of copyright holders, thereby violating intellectual property rights (IPR). This study employs a normative juridical method, drawing on a literature and statutory approach, to analyze how the distribution of digital books via shadow libraries affects copyright and how Indonesian law regulates and enforces such protection. The analysis indicates that e-books are protected under copyright law, as stipulated in Law No. 28 of 2014 and the Electronic Information and Transactions Law (UU ITE). The Indonesian government has the authority to block infringing websites as a measure to safeguard creators' economic and moral rights. The findings emphasize the importance of effective law enforcement and public awareness of the ethical distribution of content in the open information era.